The Rise of Posthumanism in Marine Ecotourism: A Comprehensive Bibliometric Analysis - Prihadi, Donny Juliandri; Lahbar, Ghulam Murtaza (Journal of Posthumanism, 2025)
This study explores the intellectual landscape of posthumanism in the context of ecotourism and sustainability through a bibliometric and keyword co-occurrence analysis using VOSviewer. By mapping the collaboration networks of authors and countries, and visualizing the co-occurrence of key terms, the research identifies the most influential contributors, emerging thematic clusters, and interdisciplinary linkages within the field. The study reveals that authors from the United Kingdom, Canada, and Australia are central to scholarly collaborations, while thematic clusters show an integration of critical theory, environmental justice, and sustainable development. Keyword analysis highlights the growing traction of philosophical and ecological terms that emphasize more-than-human perspectives in tourism research. These findings underscore the importance of rethinking traditional tourism paradigms and advocate for a more inclusive, relational, and sustainable approach to ecotourism grounded in posthumanist ethics.